PENGARUH TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP PENURUNAN TINGKAT KECEMASAN PADA LANSIA SELAMA MASA PANDEMI COVID-19 - Sakiyan, Mugihartadi (Jurnal Ilmiah Keperawatan, 2020)
The death rate due to the Covid-19 virus based on the World Health Organization (WHO) dated April 19, 2020 was 152,551 people (WHO, 2020). According to data from the Ministry of Health, the percentage of confirmed positive Covid-19 on 27 May 2020 was 23,851 cases, and 1,473 cases died. Elderly people often experience psychological disorders such as stress, depression and anxiety, especially in the face of the Covid-19 outbreak because a lot of information about the Indonesian population has been confirmed positive and causes death to increase the level of anxiety. Efforts in overcoming anxiety that occurs in the elderly can be done with SEFT spiritual relaxation. Objective: To analyze the effect of Spiritual Emotional Freedom Technique (SEFT) therapy on reducing anxiety levels in the elderly in Grantung Village, Bayan District, Purworejo Regency. Methods: This type of research used a pre-experimental research design with one group pretest-posttest design. The sampling technique used total sampling with a sample size of 79 elderly in Grantung Village, Bayan District, Purworejo Regency. The data analysis technique used the Wilcoxon Signed Rank Test. The research instrument used HARS questionnaire sheet and SEFT therapy SOP. Results: The results showed that most of the anxiety levels of the elderly before being given SEFT therapy were in the moderate category of anxiety and after being given SEFT therapy, most of the anxiety levels in the elderly decreased to the mild category. Conclusion: There is an effect of SEFT therapy on the level of anxiety in the elderly during the Covid-19 pandemic in Grantung Village with a value of p = 0.000 (p value <0.05). Recommendations:for the elderly should apply SEFT therapy independently to deal with anxiety problems during the pandemic Covid-19.